Антитіла до рецептора тиреотропіну за патології щитоподібної залози - Oliynyk, V.A.; Strafun, L.S. (Ендокринологія | Endokrynologia, 2020)
Антитіла до рецептора тиреотропіну за патології щитоподібної залози